The Usefulness of Intrapartum Transperineal Ultrasonography for the Prediction of Mode of Delivery - Saridogan, Erdinc; Moraloglu Tekin, Ozlem (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: We aimed to assess the accuracy of intrapartum transperineal ultrasonography that is non-invasive, easy to learn, rapid to perform, comfortable for pregnant women, and low-cost method to evaluate the progress of labor objectively. STUDY DESIGN: We evaluated two hundred-ten singleton pregnant women at term with cephalic presentation who went into active labor via intrapartum transperineal ultrasonography using the angle of progression and head-perineum distance. Maternal characteristics, conventional vaginal examination findings, mode of delivery, and neonatal results were noted. The data were compared using correlation and regression analysis. RESULTS: The relationships between the descent of clinical fetal head station, the increase of angle of progression (p=0.001), and the decrease of head-perineum distance (p=0.001) were statistically significant. The receiver operating characteristics curve showed that measurement of angle of progression with <110.5 degrees (p=0.001) and measurement of head-perineum distance with >52.5 millimeters (p=0.001) were associated with emergent cesarean delivery. For the prediction of delivery mode, both angle of progression and head-perineum distance had high sensitivity and specificity. CONCLUSIONS: Intrapartum transperineal ultrasonography parameters were in agreement with each other and conventional vaginal examination for determination of delivery mode. Head-perineum distance was a parity-dependent measurement whilst angle of progression was parity-independent.